ChIP-seq Profiling Identifies Histone Deacetylase 2 Targeting Genes Involved in Immune and Inflammatory Regulation Induced by Calcitonin Gene-Related Peptide in Microglial Cells - Xingjing Guo; Dan Chen; Shuhong An; Zhaojin Wang (Journal of Immunology Research)
Calcitonin gene-related peptide (CGRP) is a mediator of microglial activation at the transcriptional level. The involvement of the epigenetic mechanism in this process is largely undefined. Histone deacetylase (HDAC)1/2 are considered important epigenetic regulators of gene expression in activated microglia. In this study, we examined the effect of CGRP on HDAC2-mediated gene transcription in microglial cells through the chromatin immunoprecipitation sequencing (ChIP-seq) method. Immunofluorescence analysis showed that mouse microglial cells (BV2) expressed CGRP receptor components. Treatment of microglia with CGRP increased HDAC2 protein expression. ChIP-seq data indicated that CGRP remarkably altered promoter enrichments of HDAC2 in microglial cells. We identified 1271 gene promoters, whose HDAC2 enrichments are significantly altered in microglia after CGRP treatment, including 1181 upregulating genes and 90 downregulating genes. Bioinformatics analyses showed that HDAC2-enriched genes were mainly associated with immune- and inflammation-related pathways, such as nitric oxide synthase (NOS) biosynthetic process, retinoic acid-inducible gene- (RIG-) like receptor signaling pathway, and nuclear factor kappa B (NF-κB) signaling pathway. The expression of these key pathways (NOS, RIG-I, and NF-κB) were further verified by Western blot. Taken together, our findings suggest that genes with differential HDAC2 enrichments induced by CGRP function in diverse cellular pathways and many are involved in immune and inflammatory responses.